Types of Mastectomies and Immediate Reconstructions for Ipsilateral Breast Local Recurrences - Simon, Pauline; Barrou, Julien; Cohen, Monique; Rua, Sandrine; Lambaudie, Eric; Houvenaeghel, Gilles (Frontiers in Oncology, 2020)
Purpose: Ipsilateral-breast-local-recurrence (ILBLR) is a rare event with little data on immediate-breast-reconstruction (IBR). We report post-operative results of different types of mastectomy for ILBLR with or without IBR performed during a period of 40 months in order to analyze post-operative complications as main objective. Methods: We analyzed mastectomies performed for ILBLR after initial breast conservative treatment from January 2016 to April 2019. The characteristics of patients, surgery, complication rate, postoperative hospitalization have been determined. Results: Of the 207 mastectomies, 32.8% had an IBR: 31 nipple-sparing-mastectomy (NSM) and 37 skin-sparing-mastectomy (SSM) with 37 latissimus-dorsi-flap (LDF) IBR and 31 implant-IBR. Few reconstruction was performed for patients with body-mass-index ≥30 (OR=0.214), infiltrating ductal carcinomas (OR=0.272) and ASA-3 patients (OR=0.254). In multivariate analysis, LDF-IBR was more often realized for NSM and for patients with BMI ≥25. The overall complication rate was 37.4%: 45.6% and 33.1% with and without IBR, respectively (p=0.056). In multivariate analysis, BMI ≥25 (OR 2.02 p=0.023), IBR (OR 1.9, p=0.046) and tobacco (OR 2.17, p=0.055) were correlated with higher risk of complications. There was no difference for Grade 2-3 complications rates for IBR and no IBR, respectively (14.7%: 10/68 and 9.3%: 13/139). In multivariate analysis, overall survival from date of mastectomy for local recurrence was significantly associated with interval time to local recurrence (OR 6.981). Conclusion: Salvage mastectomy and IBR is a good choice for ILBLR, particularly using flap reconstruction. NSM can be considered as a good option in selected patients for for NSM and/or LDFR.